Sexual Dysfunctions among Male Schizophrenic Patients Attending Al- Rashad Sex Clinic - Shakir, Aziz Salim; Marzook, Ahmed Abed; Kadim, Jameel; Khalid, Hasan; Jassam, Mohammed Dawood (AL-Kindy College Medical Journal, 2013)
Background: Sexual dysfunction in patients with schizophrenia was reported as one of the most distressing antipsychotics drug adverse effects and it is directly related to treatment compliance, but the subject seldom touched in the field of psychiatry in Iraq previously.Objectives: To assess and find out the impact of schizophrenia on Sexuality of the patient, and illustrate effect of anti-schizophrenic on sexual activityMethods: using DSM4-TR and ASEX scale questionnaires for 104 male participants from out 155schizophrenic patient were studied in sex clinic in Al-Rashad teaching hospital for psychiatric disease in Baghdad. The study extended for 22 months from 1st of July 2010 to the 1st of April 2012, t test and chi square test were used for statistical analysis. P ≤0.05 used as cutoff point of significance.Results: fifty-five percent of schizophrenic male in this study got sexual dysfunction, their ages extended from (18-66 y) with mean 47year,there was significant association between age and sexual function (p- 0.018), although only 17%(18 out of 104) got secondary school education or higher ,but there is significant association between getting better educational level and better sexual function (p 0.001), results showed that low socioeconomic status got worse effect on sexual function(p 0.044) and so when being unemployed (p 0.001)combination of antipsychotic with antidepressants, may cause sexual dysfunction (P 0.036) ,and the more the duration of treatment the worse the effect on sexuality(P 0.001). When patients classified by type of sexual disorder:-desire disorder 19%, arousal disorder 28%, orgasm disorder 24%and sexual dissatisfaction with partner 29%.Conclusions: sexual dysfunction in schizophrenics is rather common though shadowed in our community for cultural, religious reasons and stigma of schizophrenia itself, so that evaluating sexual dysfunction should be routinely inquired from patients with schizophrenia receiving antipsychotics medication during follow up and dosage adjustment.